Fiesta de mamacha Cocharcas - Poredoš, Miha (Etnolog. Nova vrsta (Ljubljana), 2013)
The feast of the Virgin of Cocharcas, patron saint of Sapallanga, is one of the most important days of the calendar year, which spread from Bolivia to Peru by way of trade routes. It replaced the pre-Hispanic spring festival of the fertility goddess Coya Raymi. The inhabitants of the village perform a variety of tasks during the feast to preserve and reaffirm the reciprocity between the Virgin and the community. They achieve this by participating in the organisation and execution of the feast: as officials responsible for the images, sponsors of the dance groups, performers of folklore dances, or in some other way. Successful collaboration in the feast strengthens the ties between the individuals and the community, establishes and confirms their social status and ethnic identity. This requires riches and affluence to be distributed as is manifested through the folklore dances. This way of sacrificing to and worshipping Our Lady enables a new cycle of accumulating material wealth, creates a feeling of reciprocity and preserves and reaffirms the community's collective memory.
Keywords: ethnology; etnologija; anthropology; antropologija; Peru; ljudska verovanja; ljudski prazniki; rituali